2011
DOI: 10.2174/1874285801105010091
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of ESBLs Producing Klebsiella pneumoniae Isolates in Some Major Hospitals, Iran

Abstract: Aims of this study were to investigate on antibiotic resistance and molecular epidemiology of K.pneumoniae producing ESBLs isolates of respiratory tract infections in some major hospitals in Iran. K.pneumonaie were obtained of patients with RTI. K. pneumoniae producing ESBLs detected by screening, confirming and PCR methods. During the 12-month period, a total of one hundred and thirteen of K.pneumoniae were found from RTI in three cities in different region of Iran which Sixty seven strains (59.2%) were ESBLs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
37
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 14 publications
7
37
4
Order By: Relevance
“…A study conducted by Ghafourian et al (24) in 2011 in Iran determined that 94% of K. pneumoniae strains carried the bla SHV gene, which is in parallel with our results (24) . In recent years, the high relative prevalence of the bla SHV gene in ESBL-producing K. pneumoniae strains has been reported worldwide.…”
Section: Discussionsupporting
confidence: 91%
“…A study conducted by Ghafourian et al (24) in 2011 in Iran determined that 94% of K. pneumoniae strains carried the bla SHV gene, which is in parallel with our results (24) . In recent years, the high relative prevalence of the bla SHV gene in ESBL-producing K. pneumoniae strains has been reported worldwide.…”
Section: Discussionsupporting
confidence: 91%
“…The results obtained from this study showed a high resistance of K. pneumonia isolates to cefixime, cefotaxime, ceftriaxone, ceftazidime, and trimethoprim/sulfamethoxazole. This is similar to recent articles in which resistances ranged between 50% and 99% for cefotaxime (3,28) and was up to 20% for trimethoprim-sulfamethoxazole (29). In our hospital, the high resistance of K. pneumonia to cefixime, cefotaxime, ceftriaxone, and ceftazidime was a disturbing finding since these are among the most widely used empirical therapies for febrile infections such as UTI.…”
Section: Discussionsupporting
confidence: 91%
“…The rate of detection of ESBLs in K. pneumoniae was calculated to be 42.68%; this was lower than the rate observed in Iran (59.20%), and higher than that seen in Beijing (32.21%). However, the rate of detection of CTX-M ESBLs in ESBL-positive K. pneumoniae (87.62%) was similar to that seen in Beijing (84.80%), and higher than that in Iran (23.90%) (Feizabadi et al, 2010;Ghafourian et al, 2011;Zou et al, 2011;An et al, 2012). Therefore, we concluded that the production of ESBLs and CTX-M ESBLs differed regionally; this may be attributed to the increasing habit of antibiotic use, or the choice of detection method.…”
Section: Discussionmentioning
confidence: 50%